New species of Oculatella (Synechococcales, Cyanobacteria) from terrestrial habitats of Ukraine - Vinogradova, O.M.; Mikhailyuk, T.I.; Glaser, K.; Holzinger, A.; Karsten, U. (Український ботанічний журнал, 2017)
Here we describe two new species of Oculatella Zammit, Billi & Albertano from terrestrial habitats of Ukraine: O. ucrainica sp. nov. and O. kazantipica sp. nov. The strains were isolated from biological crusts collected at the Sea of Azov conqina beach, and both clay slopes and chalk outcrops in the Kharkiv Region. Five strains evaluated in this study phenotypically and phylogenetically differed both among each other and from other species of this genus. On the phylogenetic tree based on 16S rRNA gene sequence comparison, original strains joined already known species of Oculatella forming isolated lineages, one of which joined the group of drought-resistant terrestrial species (O. ucrainica), while another (O. kazantipica) grouped together with terrestrial O. neakameniensis Kováčik et Johansen and aquatic O. hafneriensis Kováčik et Johansen. The phylogeny based on the 16S rRNA gene concatenated with the 16S-23S ITS region, as well as secondary structures of the most informative helices of the 16S-23S ITS confirmed new species designation. Filaments of O. ucrainica are narrower (1.5–3.0 μm), and trichomes are wider (1.3–2.7 μm) comparing to O. kazantipica (its filaments are 1.3–7.5 μm wide, trichomes 1.1–1.7 μm wide). The new species also differ from one another in sheath morphogenesis, appearence of trichomes, and cell length. Oculatella ucrainica morphologically and phylogenetically is close to desert species O. coburnii Pietrasiak et Johansen, differing in the higher degree of sheath formation, wider trichomes, apical cells without irregular outgrowth, and by composition and secondary structure of 16S-23S ITS region. O. kazantipica is similar to O. hafneriensis and O. neakameniensis, from which it differs in more abundant sheath, false branching, granulations at cross walls, longer intercalary cells, and by composition and secondary structure of its 16S-23S ITS region. Описані нові для науки види з роду Oculatella Zammit, Billi & Albertano: O. ucrainica sp. nov. та O. kazantipica sp. nov., виділені з біологічних кірочок, відібраних на ракушняковому пляжі біля Азовського моря (АР Крим), а також на крейдяних та глинистих схилах у Харківській області. Комплексне дослідження п'яти отриманих штамів Oculatella показало, що фенотипично та філогенетично вони відрізняються від усіх відомих видів цього роду. На філогенетичному дереві, побудованому на основі порівняння послідовностей генів 16S рРНК, штами нових видів приєднались до вже відомих видів Oculatella, які утворювали окремі лінії, при цьому один з них (O. ucrainica) увійшов до групи засухостійких наземних видів, а інший (O. kazantipica) потрапив до однієї клади з терестріальним видом O. neakameniensis Kováčik et Johansen та озерним O. hafneriensis Kováčik & Johansen. Філогенетичний аналіз за ділянкою 16S рРНК, зв'язаною з регіоном 16S-23S ITS, а також вторинні структури найінформативніших хеліксів 16S-23S ITS підтвердили виділення нових видів, які морфологічно також чітко відрізняються. Нитки O. ucrainica вужчі (1,5–3,0 мкм), а трихоми ширші (1,3– 2,7 мкм), ніж у O. kazantipica (нитки 1,3–7,5 мкм шир., трихоми 1,1–1,7 мкм шир.), є відмінності у морфогенезі піхов, перетягнутості трихомів та довжині клітин. Oculatella ucrainica найбільш подібний до пустельного виду O. coburnii Pietrasiak & Johansen, від якого відрізняється інтенсивністю формування піхов, ширшими трихомами, відсутністю неправильного виросту на кінцевих клітинах, а також конфігурацією вторинної структури регіону 16S-23S ITS. Oculatella kazantipica близька до O. hafneriensis та O. neakameniensis, від яких відрізняється за морфологією піхов, наявністю несправжнього галуження, грануляціями біля поперечних перегородок, більшою довжиною інтеркалярних клітин, та деталями будови вториннної структури регіону 16S-23S ITS. Описаны новые для науки виды из рода Oculatella Zammit, Billi & Albertano: O. ucrainica sp. nov. и O. kazantipica sp. nov., выделенные из биологических корочек, отобранных на ракушечниковом пляже у Азовского моря (АР Крым), а также на меловых и глинистых склонах в Харьковской обл. Комплексное исследование пяти полученных штаммов Oculatella показало, что фенотипически и филогенетически они отличаются от всех известных видов этого рода. На филогенетическом дереве, построенном на основе сравнения последовательностей генов 16S рРНК, штаммы новых видов присоединялись к уже известным видам Oculatella, образующим отдельные линии, при этом один из них (O. ucrainica) вошел в группу засухоустойчивых наземных видов, а другой (O. kazantipica) попал в одну кладу с наземным видом O. neakameniensis Kováčik et Johansen и водным O. hafneriensis Kováčik & Johansen. Филогенетический анализ по участку 16S рРНК, связанному с регионом 16S-23S ITS, а также вторичные структуры наиболее информативных хеликсов 16S-23S ITS подтвердили выделение новых видов, которые морфологически также хорошо различимы между собой. Нити O. ucrainica ýже (1,5–3,0 мкм), а трихомы шире (1,3–2,7 μm), чем у O. kazantipica (нити 1,3–7,5 мкм шир., трихомы 1,1– 1,7 мкм шир.), отличия также касаются морфогенеза влагалища, перешнурованности трихомов и длины клеток. Oculatella ucrainica наиболее сходен с пустынным видом O. coburnii Pietrasiak & Johansen, от которого отличается интенсивностью формирования влагалища, более широкими трихомами, отсутствием неправильного выроста на конечных клетках, а также конфигурацией вторичной структуры региона 16S-23S ITS. Oculatella kazantipica близка к O. hafneriensis и O. neakameniensis, от которых отличается морфологией влагалища, наличием ложного ветвления, грануляциями у поперечных перегородок, большей длиной интеркалярных клеток и деталями строения вторичной структуры региона 16S-23S ITS.